A new water quality index elaborated under the brazilian legislation perspective. Issue 3 (3rd July 2022) - Cicilinski, Alana Deduck; Virgens Filho, Jorim Sousa
ABSTRACT: The main objective of this work was the development and evaluation of usage of a new water quality index (WQI) that linked the information of the parameters that compose it and the practicality of calculation to the current legislation in Brazil. For this, 30 water monitoring stations were selected, in the hydrographic unit of Upper Iguaçu-Parana-Brazil. Three methods of WQIs calculation were applied: National Sanitation Foundation- NSF (WQINSF), Bascaran (WQIb), and the new method proposed called Bascaran-CONAMA (WQIc). The calculation of the WQIc was adapted based on the WQIb and had its parameters based on Brazilian legislation (CONAMA 357). Statistical analysis at a significance level of 1% was performed in the comparison of the three indexes, by monitoring station and seasonal periods. It was verified that the results obtained through the calculation of the new index proposed had a greater coherence with the Brazilian scenario. Keywords: Brazilian Water Quality Index; Water Pollution; Watersheds Monitoring.